2018
DOI: 10.1016/j.nmni.2018.07.003
|View full text |Cite
|
Sign up to set email alerts
|

Pathogenicity locus determinants and toxinotyping of Clostridioides difficile isolates recovered from Iranian patients

Abstract: Little is known about the toxin profiles, toxinotypes and variations of toxin Clostridioides difficile C (tcdC) in Iranian C. difficile isolates. A total of 818 stool specimens were obtained from outpatients (n = 45) and hospitalized patients (n = 773) in Tehran, Iran, from 2011 to 2017. The 44 C. difficile isolates were subjected to PCR of toxin C. difficile A (tcdA), toxin C. difficile B (tcdB), tcdA 3′-end deletion, toxinotyping and sequencing of the tcdC gene. Thirty-eight isolates (86.36%) were identified… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 35 publications
2
4
0
Order By: Relevance
“…Sequence analysis of tcdC, predicted that six variants (35/50, 70%) were present in our studied isolates. Recently, Aliramezani et al identi ed two tcdC variants out of 38 isolates including tcdC-sc3 (44.73%) and tcdC-A (18.43%) genotypes [32]. In that study, 36.84% of the isolates were identi ed as a wild-type tcdC genotype which is similar to our ndings.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Sequence analysis of tcdC, predicted that six variants (35/50, 70%) were present in our studied isolates. Recently, Aliramezani et al identi ed two tcdC variants out of 38 isolates including tcdC-sc3 (44.73%) and tcdC-A (18.43%) genotypes [32]. In that study, 36.84% of the isolates were identi ed as a wild-type tcdC genotype which is similar to our ndings.…”
Section: Discussionsupporting
confidence: 90%
“…The PCR ribotypes of isolates within toxinotype 0 were classi ed into 13 RTs and largely belonged to 001/0, whereas the majority of toxinotype V isolates consisted of the 126/V type. Our ndings resemble a recent study from Iran, in which the toxinotypes 0 (81.57%) and V (18.42%) were reported as the most common toxinotypes [32]. Moreover, another study from diarrheic individuals in an Iranian hospital reported toxinotypes 0 and V as the most prevalent types [33].…”
Section: Discussionsupporting
confidence: 87%
“…The toxigenic type A + B + is the most common among toxigenic types [35,36]. However, the presence of tcdA 3 -end deletion has been detected in many clinical isolates, resulting in toxin A-negative C. difficile isolates [37,38]. About half of C. difficile isolates collected during 2006-2009 (THA group) were toxigenic with the highest occurrence of A -B + isolates (Figure 1A).…”
Section: Discussionmentioning
confidence: 99%
“…In this study, the CE-ribotyping profile of this isolate did not correspond to any type of the previously known profiles in the ECDC-Leeds-Leiden reference C. difficile strain dataset (data not shown). However, toxinotyping revealed that this C. difficile belonged to toxinotype V which was also observed in 18.4% of the Iranian C. difficile isolates obtained from stool specimens of patients suffered from CDI [52]. One study was conducted in Iran in 2015 for detection of C. difficile in WWTPs.…”
Section: Discussionmentioning
confidence: 99%